Smoking frequency of the women in two training and research health regions in Elazi? city centre - Gülbayrak, Canan; Açik, Yasemin; Deveci, Süleyman Erhan; O?uzöncül, Ayşe Ferdane (My University, 2004)
Purpose: Smoking is one of the preventable death causes in females. In developing countries, the smoking frequency of females is increasing day by day. This study, carried out in two Training and Research Health regions in Elazig city centre, was aimed to determine the smoking frequency of the women living there. Material and Methods: A total of 264 people determined with a confidence interval of 95% and living in the Training and Research Health Department region in January 2003 constituted the study population of this study. The women selected from the Health Department records with Randomised Numbers Scale were applied a questionnaire form composed of multiple-choice questions. Results: The smoking rate of the women who participated in the research was 26.5% and the mean age of beginning smoking was 20.0±4.8 years. The mean cigarette numbers consumed by the women 10.6±6.8 a day. Thirty five point seven percent consumed 6-10 cigarettes a day. While the highest smoking rate was in the group aged 25 years and under (33.1%), it reduced as age increased. Fiftyfour point eight percent of working women and 22.7% of housewives still smoke (p=0.001). It was determined that as the level of education increases, the smoking rate also increases (p=0.0001). Conclusion: In this study, the proportion of women's cigarette smoking is high. This proportion becomes at a higher young age, high education level and women working in an income providing job.
Elazi? i?l merkezi?nde i?ki? e?i?ti?m araştirma sa?lik oca?i bölgesi?nde kadinlarin si?gara i?çme sikli?i
Keywords: Smoking; Women